Sustainable Development Goal 5: Legal Frameworks & Policies To Promote, Enforce & Monitor Gender Equality In India & Japan - Ms. Aishwarya Thakkar, Dr. Kavita Sindhav (South Eastern European Journal of Public Health, 2025)
Abstract India and Japan are two of the fastest-growing economies globally and are in a strong competition for the 4th position in the world’s economic rankings. Currently, India ranks as the 5th largest economy, with a GDP of around 3.7 trillion. By 2025, India is projected to overtake Japan and become the fourth-largest economy in the world. April 1952, being the mark of diplomatic relations as the beginning between Japan & India, since then it’s not a hidden fact that the relation between both the countries have matured in areas of cooperation in the field of politics, defence, security, economic, science & technology, education, culture & integration of people across borders. The Impact of the 6th century beginning with Buddhism in Japan & filtered Indian culture from Buddhism has had a great impact in bringing closeness between India & Japan. However, if we look at Japan, it is coined as a Developed Country whereas India is still in the category of developing country. Also, if we look at SDG rankings, India is ranked at 109th Position & which is far behind the ranking of Japan which is at 18th Position amongst 166 nations. According to a recent survey amongst 146 countries on gender equality & gender gap, reports say that both India & Japan are struggling in this SDG goal & needs to work a lot towards working towards the same & providing equal opportunity & rights irrespective of gender. Based on the report Japan stands at 118th position & India Stands at 129th position if ranked for gender equality. Major North American, European & some Asian countries are surpassing Japan & India by accelerating their efforts towards reducing gender cap & taking impactful actions in direction of gender world bank collection of development indicators report Japan has 51.41% women population & India has 48.42% of Indian population. Overall, gender equality is not only a basic human right but also crucial for fostering peaceful societies, unlocking full human potential, and promoting sustainable development. Moreover, there are various studies & reports showing that women empowerment spurs productivity & economic growth. In conclusion, even if countries ensure more than 50% participation from the total women population a lot of difference & impact can be made in gender equality & inclusive countries leading to a lot of economic, social & cultural advancements for the country’s equality.